Effect of hemodialysis in end-stage renal disease patients on pulmonary function tests: a meta-analysis of cross-sectional studies - Zhang, Qing; Xu, Youyou; Huang, Dan; Jiang, Jiaru; Jiang, Sicong; Wu, Huichao (Frontiers in Physiology, 2026)
BackgroundHemodialysis, the principal therapy for end-stage renal disease (ESRD), directly influences pulmonary mechanics by alleviation of fluid overload and uremic toxin accumulation. Hemodialysis (HD), the main renal replacement therapy, removes excess volume and solutes, but its acute effects on pulmonary function remain uncertain. This meta-analysis evaluates impact of hemodialysis on pulmonary function and examines pre-to post-dialysis changes in spirometric parameters among ESRD patients.MethodsWe conducted meta-analysis of cross-sectional studies that measured pulmonary function in ESRD patients on maintenance hemodialysis. Data from 16 eligible studies (n = 719 patients) were synthesized. Our analysis was focused on changes in forced expiratory volume in 1 s (FEV1), forced vital capacity (FVC), FEV1/FVC ratio, forced expiratory flow at 25%–75% (FEF25-75), and peak expiratory flow rate (PEFR). Statistical analysis was performed using random-effects models to calculate pooled mean differences (MD) for spirometric outcomes.ResultsHemodialysis was associated with significant improvements in percent-predicted FEV1 (+8.99%) and FVC(+12.87%), while absolute changes in these parameters were small and not statistically significant. The FEV1/FVC ratio and PEFR also improved in percent-predicted terms. Sensitivity analyses confirmed stability of results, though high heterogeneity (I2>75%) was observed for several outcomes. Publication bias was minimal, with Egger’s and Begg’s tests indicating no significant asymmetry, except for borderline Begg’s p-value for FVC (%pred). These improvements likely reflect ultrafiltration-mediated relief of pulmonary congestion and modulation of uremic milieu.ConclusionHemodialysis acutely mitigates renal failure-related pulmonary restriction, with percent-predicted spirometry showing consistent gains. These effects highlight role of dialysis prescriptions and fluid management strategies in optimizing respiratory as well as renal outcomes.